Análise dinâmica de torres e estruturas elevadas lateralmente carregadas - Oliveira, Romilde Almeida de (1974)
The dynamic response of tall building is studied for two different behaviors of structures: a cantilever beam and a shear building. The wind action is supposed to be deterministic. A viscous type damping is introduced and the general equations of the motion are obtained from the Hamilton Principle. Some considerations are done on the nature of the damping matrix, by means of specifying the percentage of critical damping, uncoupling of damped systems and methods for the calculation of the eigenvalues. An automatic computer program is developed to provide the dynamic characteristics and response to several types of loading. The program is written in FORTRAN for the IBM/360 computer.